The role of learning technology developers as facilitators during the Covid-19 pandemic - Susilo, Joko; Suryono, Hasan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
Innovation in the learning technology field to facilitate the activities of students and educators in the learning process is the task and responsibility of the Learning Technology Developer (Pengembang Teknologi Pembelajaran/PTP). This research aims to (1) describe and analyze the role of PTP as a facilitator in online learning during the Covid-19 pandemic and (2) describe PTP products in online learning during the Covid-19 pandemic. The research method used is descriptive qualitative. The research results show that PTPs, as facilitators, must be creative and innovative in developing learning models, media, and applications, collaborating with other professions, and increasing existing competencies related to cutting-edge technology and media. PTP must prove its performance through real work that can be realized through appropriate learning models, media, and applications. PTP has two main areas of study: soft technology and hard technology. The products produced by PTP can take the form of ICT-based learning models, learning media, and e-learning applications.